Dirofilariasis in stray dogs in southern Russia: improvement of laboratory studies - Mrs Julia Kiosova; Ms Sergey Nagorniy; Mrs Larisa Ermakova; Mrs Telicheva Victoria; Ms Igor Kornienko; Ms Vadim Melnik (International Journal of Infectious Diseases)
Introduction: Dirofilariasis is a relatively new medical problem caused by changes in natural, climatic and social conditions. Methods: In 2023, venous blood of 233 dogs was collected from shelters for homeless animals in the city of Rostov-on-Don and the Rostov region. Testing the blood of dogs for dirofilariasis was carried out using two Methods: the morphological (Knott's method with 3% acetic acid solution) and real-time polymerase chain reaction (RT-PCR). RT-PCR was performed using primers developed by us for Dirofilaria repens and Dirofilaria immitis in accordance with improved isolation protocols.The preparation of the PCR mixture for the reaction was carried out using a set of reagents for RT-PCR in the presence of EVAGreen (SINTOL) with highly specific primer pairs. For D. repens: (F2690DR) 5’-АAGTGTTGATGGTCAACCTGAA-3’ and (R2812DR) 5’- GTAGAACGCATATTCTGAGT-3’. For D. immitis: (F2690DI) 5’- GAGTGTAGAGGGTCAGCCTGAG-3’ and (R2812DI) 5’- GTAGAACGTATATTCTGAAC- 3’. DNA amplification modes were selected empirically. Results: As a result of research using larvoscopy, dirofilaria larvae were found in 53 samples with an intensity of invasion from one to one hundred larvae in 0.2 ml of blood, the extent of invasion was 22.75%. The PCR method detected dirofilaria in 60 samples. The prevalence of dogs was 25.75%, of which D. repens – 21.67%, D. immitis – 41.67%, mixed invasion was 36.67%. The results obtained were analyzed in a four-field contingency table. As the analysis showed, the sensitivity of the PCR method was 90.57%, and the microscopy method was 81.36%. The specificity of the first method was 93.33%, the second – 97.13%. Discussion: Despite the increase in the quality and quantity of deworming activities for dogs, which are the most epidemiologically significant source of dirofilaria infection, in recent decades there has been an increase in the prevalence of these nematodes in definitive hosts in Europe. The expansion of the range of dirofilariasis has been facilitated by animal migration and climate change, which affects mosquito vectors. The main factor in the unfavorable epidemiological situation is the significant number of stray dogs infected with dirofilaria that have not undergone veterinary examination. Direct diagnostic methods remain the «gold standard», but require highly qualified specialists. The polymerase chain reaction (PCR) method is also a direct diagnostic method that can detect the DNA of parasitic pathogens in various biological substrates. Conclusion: The results of our study indicate a continuing high risk of dirofilariasis in the population of a number of regions of southern Russia. The main cause of epizootological problems remains the high intensity of invasion of animals not covered by veterinary examination.The developed test system allows you to determine the presence of two species of dirofilaria in real time and in a short time. This system can improve the work of veterinary laboratories.